Great power politics in contemporary East Asia : negotiating multipolarity or hegemony? - Tan, See Seng (2009)
Perceptions among academics and analysts of great power politics in contemporary East Asia vary. In theoretical terms, some have described the East Asian region as multipolar, where balancing relations between China, Japan and United States potentially threaten to undermine existing multilateral processes as well as the stability in the region. Others have argued that the region is better described as unilateral in view of the preponderant power of the US, the sole global superpower. Futher, the Bush Administration's missile defense (MD) policy, among other things, underscores Washington's penchant towards unilateralism. Against this backdrop, this paper makes two arguements. First, an aggressive effort by the US to deploy MD will likely destabilize the East Asian region. Second, all three great powers (China, Japan and the US) must necessarily exercise reason, restraint, and responsibility in their policy making and implementation, or face the sobering prospect of East Asia as a likely future setting of great power conflict.